Construction of 3-Nitrocarbazoles via Domino Henry Reaction/Dehydration/Benzannulation of 2-Alkynylindole-3-carbaldehydes - Raji Reddy, Chada; Saiprasanna, Namburi Lakshmi; Karuna Sagar, Banoth; Nair, Karna; Kota Balaji, Shiva Kumar (Synthesis, 2025)
A novel domino reaction, involving Henry reaction, dehydration, and intramolecular benzannulation of 2-alkynylindole-3-carbaldehydes with nitromethane, has been developed for the synthesis of 3-nitrocarbazoles. This conversion displays good synthetic efficacy, allowing the formation of two carbon–carbon bonds under similar basic conditions. Further transformation of the 3-nitrocarbazole to indolo[3,2-b]carbazole was also demonstrated.
Keywords: Carbazole; Henry reaction; Benzannulation; Domino reaction; indolo[3,2-b]carbazole